2023
DOI: 10.3390/cryst13081212
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Calcium and Magnesium Phosphate Crystals in Stones Treated with Diammonium Hydrogen Phosphate Conservation Product: Potential of Micro-Raman Spectroscopy

Claudia Conti,
Léa Cutard,
Alessandra Botteon
et al.

Abstract: This study is aimed at investigating crystals (calcium and magnesium phosphates) formed due the interaction of an inorganic conservation treatment (diammonium hydrogen phosphate—DAP) with carbonatic (calcitic and dolomitic) stones through micro-Raman Spectroscopy. The addressed questions concern (i) the identification of magnesium and calcium phosphate minerals crystallized within dolomitic stone samples with a different degree of conservation state and treated with two different DAP solution molarities and (i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Recent studies have investigated the crystal-chemistry and 2D distribution of newly formed calcium oxalates and calcium phosphates formed by AmOx and DAP with lab-scale instruments and large-scale sources 13,15,17,20,22,23,48 and have shown that a lot of variables (e.g., the minerals, microstructure and grain size of the substrate; pH; free calcium ion availability, etc.) affect the reaction of inorganic treatments with stone materials.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have investigated the crystal-chemistry and 2D distribution of newly formed calcium oxalates and calcium phosphates formed by AmOx and DAP with lab-scale instruments and large-scale sources 13,15,17,20,22,23,48 and have shown that a lot of variables (e.g., the minerals, microstructure and grain size of the substrate; pH; free calcium ion availability, etc.) affect the reaction of inorganic treatments with stone materials.…”
Section: Introductionmentioning
confidence: 99%